2023
DOI: 10.3389/fpubh.2023.1216810
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between burnout, general wellbeing, and psychological detachment with turnover intention in Chinese nurses: a cross-sectional study

Abstract: BackgroundIt is critical to minimize nurse turnover to improve the quality of care and patient safety. In-depth investigation is required to better understand the factors related to nurses' turnover intentions.AimThis study aimed to determine the relationships between burnout, general wellbeing, and psychological detachment with turnover intention among nurses in China.MethodsA cross-sectional survey using convenience sampling was conducted in one hospital in China between January 2023 and March 2023. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Turnover intention, a willingness of employees to voluntarily leave a particular organization during the work period [ 7 ], can serve as the most effective predictor of the actual turnover behavior among nurses [ 8 ]. Meanwhile, as an important indicator to measure the quality of personal and social life, the studies found that subjective well-being can effectively improve nurses’ work enthusiasm and job satisfaction [ 9 , 10 ], and is also an important predictor of nurses’ turnover intention and actual turnover behavior [ 11 ]. Therefore, how to improve the subjective well-being of nurses and reduce their turnover intention from the perspective of positive psychology has become the focus of current nursing managers.…”
Section: Introductionmentioning
confidence: 99%
“…Turnover intention, a willingness of employees to voluntarily leave a particular organization during the work period [ 7 ], can serve as the most effective predictor of the actual turnover behavior among nurses [ 8 ]. Meanwhile, as an important indicator to measure the quality of personal and social life, the studies found that subjective well-being can effectively improve nurses’ work enthusiasm and job satisfaction [ 9 , 10 ], and is also an important predictor of nurses’ turnover intention and actual turnover behavior [ 11 ]. Therefore, how to improve the subjective well-being of nurses and reduce their turnover intention from the perspective of positive psychology has become the focus of current nursing managers.…”
Section: Introductionmentioning
confidence: 99%
“…Subjective well-being is an important index to measure the quality of personal and social life [18]. Research shows that when individuals are at a high level of subjective well-being, it has a positive impact on work performance, team cooperation and interpersonal relationship [19][20][21]. As the important factors re ecting nurses' work enthusiasm and personal experience, the importance of nurses' turnover intention and subjective well-being is self-evident.…”
mentioning
confidence: 99%